The temporal variations in the distribution of filial support from adult children to their aging parents across Europe and Israel - Zeynep Zümer Batur; Jeroen K. Vermunt; Dimitri Mortelmans; Jorik Vergauwen (PLoS ONE, 2025)
The present study aimed to investigate the temporal changes in the support provided by adult children to their ageing parents, including paperwork help, household help, and personal care, and its intensity, ranging from no support to very intense support. We used latent Markov models to assess filial support transitions. Analysing data from the Survey of Health, Ageing and Retirement in Europe (SHARE) covering 13 European countries and Israel between 2004 and 2022, we identified two types of filial support: stable and fluctuating. Our findings indicate that Austria, Germany, the Netherlands, Switzerland, France, Denmark, and the Czech Republic have a higher probability of maintaining stable filial support levels over the years. In contrast, Greece, Belgium, Italy, Spain, Israel, Sweden, and Poland exhibit fluctuating filial support. Additionally, Western and Northern countries, such as Denmark, the Netherlands, Austria, and Germany, tend to reach only moderate or intense support levels. In comparison, Southern and Eastern countries, like Italy, Spain, the Czech Republic, and Poland, provide support that can reach very intense levels.